2019
DOI: 10.1002/chem.201902221
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Fluorophosphonium Ions

Abstract: Efforts to preparea ne lusive donor-free phosphenium ion, [R 2 P] + ,l ed us to synthesize functionalized fluorophosphonium cations of the type [R 2 P(F)X] + (X = SiEt 3 ,H ,F ), which were obtained from the relatedn eutral fluorophosphines R 2 PF and R 2 PF 3 upon protonation and reaction with solvated [Et 3 Si] + ions (R = 2,6-Mes 2 C 6 H 3 ). The hypothetical reductivee limination of [R 2 P(F)SiEt 3 ] + and [R 2 P(F)H] + affording [R 2 P] + ,E t 3 SiF and HF,r espectively, was calculated to be endothermic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
8
0
4
Order By: Relevance
“…Starting from 2,6-(Me 5 C 6 ) 2 C 6 H 3 Li [12] and ECl 3 (E = P, As), we have now prepared the bis(m-terphenyl)fluoropnictogens (2,6-{Me 5 C 6 } 2 C 6 H 3 ) 2 EF (1 a, E = P; 1 b, E = As). The synthesis, solution NMR, and solid-state structural features of 1 a and 1 b resemble those of (2,6-Mes 2 C 6 H 3 ) 2 EF (E = P, [13] As [11] ) reported previously. In solution, 1 a and 1 b are characterized by 19 ] + confirmed that phosphorus was in a very similar coordination environment for both isomers.…”
supporting
confidence: 72%
“…Starting from 2,6-(Me 5 C 6 ) 2 C 6 H 3 Li [12] and ECl 3 (E = P, As), we have now prepared the bis(m-terphenyl)fluoropnictogens (2,6-{Me 5 C 6 } 2 C 6 H 3 ) 2 EF (1 a, E = P; 1 b, E = As). The synthesis, solution NMR, and solid-state structural features of 1 a and 1 b resemble those of (2,6-Mes 2 C 6 H 3 ) 2 EF (E = P, [13] As [11] ) reported previously. In solution, 1 a and 1 b are characterized by 19 ] + confirmed that phosphorus was in a very similar coordination environment for both isomers.…”
supporting
confidence: 72%
“…In this work we describe the fluoride abstraction from (2,6‐Mes 2 C 6 H 3 ) 2 PF and (2,6‐Mes 2 C 6 H 3 ) 2 AsF that proceeded most likely with the formation of the transient phosphenium ion [(2,6‐Mes 2 C 6 H 3 ) 2 P] + [ 1 a ] + and the arsenium ion [(2,6‐Mes 2 C 6 H 3 ) 2 As] + [ 1 b ] + , whereby two bulky m ‐terphenyl substituents prevent the formation of dinuclear donor–acceptor complexes. Using a similar strategy, we have been recently able to isolate the heavier stibenium ion [(2,6‐Mes 2 C 6 H 3 ) 2 Sb] + [ 1 c ] + and the bismuthenium ion [(2,6‐Mes 2 C 6 H 3 ) 2 Bi] + [ 1 d ] + (Scheme ) …”
Section: Methodsmentioning
confidence: 99%
“…The fluoride abstraction from (2,6‐Mes 2 C 6 H 3 ) 2 PF with [Et 3 Si] + was impaired by the exothermic formation (Δ E =−241.0 kJ mol −1 ) of the stable donor–acceptor complex [(2,6‐Mes 2 C 6 H 3 ) 2 (F)PSiEt 3 ] + . The hypothetical elimination of Et 3 SiF and formation of [(2,6‐Mes 2 C 6 H 3 ) 2 P] + [ 1 a ] + was found to be endothermic (Δ E =+40.1 kJ mol −1 ) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ausgehend von 2,6‐(Me 5 C 6 ) 2 C 6 H 3 Li und ECl 3 (E=P, As) haben wir nun die Bis‐ m ‐terphenylpniktogenfluoride (2,6‐{Me 5 C 6 } 2 C 6 H 3 ) 2 EF ( 1 a , E=P; 1 b , E=As) hergestellt. Die Synthese, Lösungs‐NMR‐ und Festkörperstruktur‐Merkmale von 1 a und 1 b ähneln denen der zuvor beschriebenen Verbindungen (2,6‐Mes 2 C 6 H 3 ) 2 EF (E=P, As). In Lösung sind 1 a und 1 b durch chemische Verschiebungen im 19 F‐NMR‐Spektrum (in CD 2 Cl 2 ) bei δ=−200.3 (E=P) und −216.0 ppm (E=As) charakterisiert, während 1 a ein 31 P‐NMR‐Signal bei δ=193.8 ppm zeigt.…”
Section: Methodsunclassified